2003
DOI: 10.1074/jbc.m304481200
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme-nonselective N-Substituted Bipiperidylcarboxamide Acetyl-CoA Carboxylase Inhibitors Reduce Tissue Malonyl-CoA Concentrations, Inhibit Fatty Acid Synthesis, and Increase Fatty Acid Oxidation in Cultured Cells and in Experimental Animals

Abstract: Inhibition of acetyl-CoA carboxylase (ACC), with its resultant inhibition of fatty acid synthesis and stimulation of fatty acid oxidation, has the potential to favorably affect the multitude of cardiovascular risk factors associated with the metabolic syndrome. To achieve maximal effectiveness, an ACC inhibitor should inhibit both the lipogenic tissue isozyme (ACC1) and the oxidative tissue isozyme (ACC2). Herein, we describe the biochemical and acute physiological properties of CP-610431, an isozyme-nonselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
220
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(231 citation statements)
references
References 54 publications
11
220
0
Order By: Relevance
“…CP-640186, an inhibitor of acetyl-CoA carboxylase [21], partially inhibited insulin release from pancreatic islets and INS-1 832/13 cells (Figures 4 and 5). Triclosan is a potent inhibitor of the enoyl-acyl carrier protein reductase enzyme of the prokaryotic type II fatty acid synthase complex.…”
Section: Inhibition Of Insulin Release By Inhibitors Of Lipogenesismentioning
confidence: 91%
See 2 more Smart Citations
“…CP-640186, an inhibitor of acetyl-CoA carboxylase [21], partially inhibited insulin release from pancreatic islets and INS-1 832/13 cells (Figures 4 and 5). Triclosan is a potent inhibitor of the enoyl-acyl carrier protein reductase enzyme of the prokaryotic type II fatty acid synthase complex.…”
Section: Inhibition Of Insulin Release By Inhibitors Of Lipogenesismentioning
confidence: 91%
“…TOFA (5-(tetradecyloxy)-2-furoic acid) was from Alexis Biochemicals. CP-640186 was from H. James Harwood at Pfizer [21]. Triclosan (5-chloro-2-(2,4-dichlorophenoxy)-phenol) was from Fluka BioChemika.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the proposed medical applications of the enzymes depends on their inhibition, which is associated with inhibition of fatty acids synthesis and stimulation of fatty acids oxidation, and which, in consequence, might reduce cardiovascular risk in metabolic syndrome. Compound CP-610431 bipiperidine derivative, and its analog of higher metabolic stability CP-640186, isolated by high-throughput screening, are such inhibitors active against both ACCase isoforms (Harwood, Jr., et al 2003). Kinetic studies on ACCase -CP-610431 complex and the crystal structure of yeast CT domain -CP-640186 complex have revealed that the binding site for these inhibitors is located on the carboxyl transferase domain (Zhang et al, 2004).…”
Section: Human Accase As Target In Diseases Treatmentmentioning
confidence: 99%
“…Second, the first Acc2 KO animals did not show a switching of fuels (i.e. change in respiratory exchange ratio [RER]), but rather an increase in Á V O 2 , which was not predicted by bioenergetics or evident with a dual Acc1 and Acc2 inhibitor in rats [12]. Recently, the Acc2 KO model was independently generated and resulted in an opposite phenotype [13].…”
Section: The Premisementioning
confidence: 99%